Surface stress evolution and cracks prevention of ingots during the upsetting process - Mi, Guofa (Array, 2019)
In this research, surface axial stress and propagation of surface transverse cracks on large ingots during hot forging process was studied using finite element modeling. The simulation results show that surface axial stress changes from compressive to tensile during the upsetting process. Large ingots which need to be upset and stretched several times are easy to form cracks at anvil overlapping part during stretching process. These surface transverse cracks are crack source and may rapidly propagate under surface axial tensile stress during the upsetting process. The effect of material, temperature, height-diameter ratio of billet, deformation speed, and friction coefficient between anvil and billet on the changing of surface axial stress was investigated. The results show that critical transformation point of surface axial stress from compressive to tensile has an obvious relationship with drum shape of the billet. In order to eliminate the surface axial tensile stress and prevent propagation of surface transverse cracks, a slim waist forging process was proposed based on the surface stress analysis. A quantitative designing method of slim waist billet was established for guiding industrial production.